Estimation of interleukin-17 levels in gingival crevicular fluid from healthy individuals, chronic gingivitis and chronic periodontitis patients using enzyme linked immunosorbent assay - Nainee, Neha; Sanikop, Sheetal; Jha, Abhilasha (International Journal of Research in Medical Sciences, 2020)
Background: Chronic Periodontitis (CP) is an infectious disease resulting in inflammation of supporting tissues of the teeth. A number of pro-inflammatory cytokines are formed against periodontopathogenic microorganisms. Interleukin-17 (IL-17) is a pro-inflammatory cytokine, implicated in numerous inflammatory and autoimmune conditions. Methods: A total of 25 periodontally healthy subjects (Group 1), 25 patients with gingivitis (Group 2) and 25 patients with CP (Group 3) were included for the study based on clinical examination. Gingival index, probing pocket depth and clinical attachment loss were recorded in all subjects. Results: The levels of IL-17 increased from healthy to gingivitis to periodontitis patients. A positive correlation was found with the IL-17 and the clinical parameters like gingival index, probing pocket depth and clinical attachment loss. Conclusions: There is a strong association between the levels of IL-17 with periodontal disease as well as with its severity and its possible use as a biomarker for inflammatory periodontal disease.